EXAMINING NEGOTIATIONS PROCESS ON THE REJECTED MARRIAGE DISPENSATION - Nidlomatum Mukhlisotur rohmah Nidlom; Michelle Andrina (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2021)
Through Law Number 16 of 2019 as an Amendment to Law Number 1 of 1974 concerning Marriage, Indonesia made a breakthrough by setting a higher minimum age for girls who want to marry from 16 to 19 in 2019. Those who wish to marry before the age of 19 must gain permission from the Court. However, the Court granted 97% of the marriage dispensation cases. Existing studies in this issue already analyze why the judges grant marriage dispensations, mainly avoiding the worst possible outcomes for the children. Based on our literature analysis, the acceptance of the marriage dispensation is more prominent because of the Maqosidus Sharia (the purpose of Islamic Law). This context leads to a fewer rejection of applications for the dispensation of marriage. We take a different route by analyzing the rejected applications to understand the Court's negotiation process leading to rejection. We collected 17 rejected marriage dispensation applications from different religious courts between 2018 and 2021 on the Court's online database. Then, we analyzed how the negotiation process occurred between the parties involved in the trial, namely between the Judge, the Petitioner (parents), and the husband/wife candidate (children) as the object of the marriage dispensation stipulation. On the other hand, analysis on the rejected cases found five main reasons for rejection: the immaturity of the husband/wife candidates, the Judge's judgment that the marriage will bring harm to the children, lack of evidence of an urgent need for marriage because of the Judge's advice, and administrative reasons.